GREEN SUPPLY CHAIN MANAGEMENT AT CULLINARY SMALL BUSINESS: SOME NOTES TO CONSIDER - Mellita, Dina; Sably Aliya; Efan Elpanso (Dinasti International Journal of Digital Business Management, 2020)
As the consumer becomes more aware of environmental issues and global warming, consumers will be asking more questions about the food they are consuming. Some regions noted that cullinary business dominated most of the existing micro, small and medium enterprises. This research aim to describe the practice of the green supply chain management among cullinary micro, small and medium enterprises in the city of Palembang. A descriptive survey was conducted at 39 culinary SMEs at Palembang, South Sumatera with 272 participants. The participants were selected from the various SMEs using purposive random sampling. The participants of the study were business owner, manager and employee of the SMEs. The results of the study show that SMEs have not practices the environmental friendly system either in production, manufacturing and distribution of food products. Majority of participants argue that the raw material in building GSCM is expensive and high cost.